Preservice Elementary Teachers' Noticing Formative Assessment - Tamba, Kimura Patar; Cendana, Wiputra (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
Pre-service teachers learn a lot about educational practice, especially regarding formative assessment, through noticing. For this reason, pre-service teachers’ noticing ability determines the learning process regarding formative assessment. Thus, understanding and analyzing pre-service teachers’ noticing skills is very important. This research is a descriptive qualitative research which aims to analyze the observations of pre-service teachers regarding formative assessment using a video. Data collection was carried out using video task analysis regarding formative assessment. This study involved 69 pre-service elementary teachers. The results of the task analysis were coded with the theoretical coding method. The results of the coding were then analyzed descriptively. The focus of noticing for pre-service elementary teachers is the greatest (71%) on the questioning loop aspect, while other aspects are less than 50% of the participants. No one pre-service elementary teachers observes the five aspects of formative assessment. For the quality of noticing an average of 2.25-2.85 or between the descriptive level and validation.The characteristics of the focus of pre-service elementary teachers’ noticing regarding formative assessment tend to focus on the questioning aspect and are not comprehensive. Most of the noticing quality of pre-service elementary teachers regarding formative assessment is still at the descriptive and validation level.